Application Of TheTheory Of Utilitarianism In Perllegal Protection For The Provision Of Compensation For Land Rights Holders Declared Abandoned For Development In The Public Interest - Devi Siti Hamzah Marpaung Marpaung (LEGAL BRIEF, 2022)
Procurement of land for the development of public interest and the determination of compensation cannot be separated from the issue of relinquishing land rights. This study aims to study and understand the implementation of compensation for land rights holders who are declared abandoned and legal protection for land rights holders who feel disadvantaged in the process of land acquisition for the public interest. In this study the author uses a normative juridical method, using a statutory approach, namely Law no. 5 of 1960 concerning Agrarian Principles and Law no. 2 of 2012 concerning Land Acquisition. The results of this study indicate that the implementation of compensation for land rights holders who have been declared abandoned for the development of public interest is carried out by identifying, researching, warning, and determining abandoned land. land, deliberation. As well as legal protection for land rights holders who feel aggrieved include; has the right to obtain data and information, the right to demand a file of rights or a claim for the determination of the development area/location, has the right to receive fair and fair compensation payments, and has the right to refuse the type and amount of compensation.